Value creation of decentralized metaverse platforms for platform economy : A case study - Haveri, Mikko (My University, 2023)
As a part of the assumed new era of internet, more commonly referred to as web3, includes the idea of a metaverse. Metaverse as a concept is multifaceted and is not limited to a single description. One form of this metaverse is one that exists as an environment, that is not directly controlled autonomously by a centralized entity. Decentralized metaverse in the form of digital platforms facilitate and give meaning to applicability of cryptocurrencies by enabling more ways to apply these into action. But what meaning does this have from the perspective of value creation? With the applicability to blockchain and other decentralized technologies, provides an understanding that the technology enabling the existence of decentralized metaverse is here to stay and the freedom of open-source technologies help to maintain this flexibly. In this research, we attempt to create a purposeful view on the value creational aspects of the decentralized metaverse. The research objectives focused on existing value creation ramifications that the cases of this research were identified to possess based on the theoretical framework presented in the chapter 2.4. This research was performed as a case study, along with theoretical framework based on a mapping review based on the contents of 4 literature reviews regarding platform economy value creation and their identified principles. The framework was defined for the purpose of the qualitative study for which 2 decentralized metaverse platforms were studied based on this. For the sake of limiting the concept of value, was this restricted to the concepts of value success categories (VSCs). The core conclusions from the performance of the value creation regarding each studied metaverse platform were that the decentralized metaverse platforms were found to be variable depending on how the metaverse platform architecture was built to support value creation, being both external and internal reasons regarding the platform. For example, the distinction by extended reality for the sake of digital platforms was not identified to have been beneficial for the value creation of decentralized metaverse platforms.

Osana oletettua internetin seuraavaa vaihetta, tuttavallisemmin Web3, sisältyy ajatus metaversumista. Konseptina metaversumi on monisäikeinen, ja ei ole selitettävissä nykyisellään vain yhden selitteen kautta. Yksi selite metaversumille on, että se toimisi hajautettuna ympäristönä vapaana keskitetystä hallinnosta. Hajautettu metaversumi digitaalisina alustoina pohjaa ja antaa merkitystä erityisesti kryptovaluuttojen hyötykäyttöön, mutta mikä tarkoitus tällä hyötykäytöllä on konkreettisen arvonluonnin näkökulmasta? Lohkoketjujen ja muiden hajautettujen teknologioiden myötä on yhä selvempää, että hajautetut metaversumit ja niiden mahdollistaman teknologian luoma pohja ovat tulleet jäädäkseen. Tästä muodostuvat avoimeen lähdekoodiin perustuvat sovellukset auttavat pitämään tätä joustavasti yllä. Tässä tutkimuksessa pyrittiin luomaan tarkoituksenmukainen kuva hajautetun metaversumin arvonluonnillisista menetelmistä. Tutkimus keskittyi kvalitatiiviseen tulkintaan, joka perustui olemassa oleviin arvonluontimekanismeihin, joita tapaustutkimuskohteina olleet hajautetut metaversumialustat nähtiin sisältävän tutkimusta varten luodun kehyksen mukaisesti. Tutkimus toteutettiin kvalitatiivisena tapaustutkimuksena perustuen teoreettiseen viitekehykseen kirjallisuuskatsauksen pohjalta, joka koostui neljästä kirjallisuuskatsauksesta ja niiden tunnistettujen ydinasioiden kartoituksesta perustuen alustatalouteen liittyvistä ja tutkituista arvonluontimekanismeista. Viitekehys tulkittiin kategorisesti. Kategorioilla mitattiin tutkittujen hajautettujen metaversumialustojen suorituskykyä arvonluonnissa kappaleessa 4. Arvonluonnin käsitteen selkiyttämistä varten tässä tutkimuksessa keskityttiin pelkästään teoreettiseen viitekehykseen. Tutkimuksen pääasialliset johtopäätökset liittyen tutkittujen metaversumialustojen suorituskykyyn vaihtelivat alustojen välillä riippuen niiden arvonluontia varten muodostetusta teknisestä arkkitehtuurista, jossa syyt olivat niin ulkoisia kuin sisäisiä liittyen tutkittuihin metaversumialustoihin. Esimerkiksi lisätyn todellisuusteknologian käyttöä digitaalisten alustojen kanssa ei suositella tämän tutkimuksen perusteella käytettäväksi hajautettujen metaversumialustojen kanssa niiden arvonluonnin parantamista varten.
Keywords: web3, metaverse, platform economy, digital platforms, decentralized finance, information technology, virtual environment, information systems